Perception of the family that existence the care of child with meningomyelocele: descriptive study - Maria Aneuma Bastos Cipriano; Ana Luiza Paula de Aguiar Lélis; Maria Veraci Oliveira Queiroz; Maria Vera Lúcia Moreira Leitão Cardoso (Online Brazilian Journal of Nursing, 2009)
Children with meningomyelocele (MMC) present special needs that require constant family care. We aimed to understand the family perception on the experience with children with MMC. This is a study of qualitative approach carried out with fifteen families from May to June 2008 through semi-structured interviews and non-systematic observations registered in field diary. The categories of analysis were: family daily care of children with meningomyelocele; difficulties in the access to the treatment and follow-up of the disease; and failure in communication. The results show that the needs of children/family extend mainly to physical, psychosocial and financial problems. The dissatisfaction is created by upset in attendance, accessibility and lack of information on the disease. We concluded that in order to minimize the problems provoked by the disease and promote the families’ reception are necessary: interdisciplinary intervention with institutional support; educational actions to improve the care and the quality of life of these patients.